Mathnawi-yi maʿnawī. Volume 4 : mujallad-i chahārum kashf al-abyāt va namāyahā - Rūmī, Jalāl al-Dīn, (Miras Maktoob, ISBN: 9789004365452., 2019)
The founder of the Mawlawiyya order of dervishes, Jalāl al-Dīn Rūmī (d. 672/1273) is the most celebrated and widely quoted mystical poet of the Persianate world. Born in Balkh in 604/1207, he was still a child when his father, a preacher, emigrated westwards with his family, moving to Malaṭya, Sivas, Akshehir, Larende and, finally, Konya. It was in Konya that Rūmī, who had also received a regular education, met the people who would give his life a decisive turn towards mysticism: first, his father's former pupil Sayyid Burhān al-Dīn Muḥaqqiq (d. 637/1239-40) and then, most of all, the celebrated mystic Shams al-Dīn Tabrīzī (d. 645/1247). Rūmī's Mathnawi-yi maʿnawī is a didactic poem inspired by his favourite student Ḥusām al-Dīn Čelebi (d. 683/1284). Composed in six fascicles ( daftar ), it took several years to complete. The edition printed here is an enhanced version of the one by Nicholson, with Nicholson's introductory essays and notes translated into Persian. 4 vols; volume 4.